(3eNJUQ HOjY aj THjgGJ GdbQBf hCeKGdgs - (3eMeO Hf CHj HcQ Hf CjhH Hf bje GdLhRjg, GHf Gdbje, TeS GdOjf, CHh YHO Gddg, J (B751 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hUdi Gddg Ydi NjQ GdHQjI eMeO hBdg CLeYjf bGd TjNfG QMeg Gddg JYGdi hbY ai GdbQBf CeKGd hCf CeKGd GdbQBf dGjYbdgG Edi GdYGdehf aEfgG THjgg TF TF ai Mceg s
(3BNQgG (B:s
(3hEdi Cgd GdfGQ jYPHhf ajgG aUd hGdWeCfjfg Edi CSeGA GdQH hUaGJg fhYGf WeCfjfg Edi GdEjeGf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B15s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B56s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
(3eLGejY s
Keywords: (3GdeLGejYs